1997
DOI: 10.1080/09397140.1997.10637741
|View full text |Cite
|
Sign up to set email alerts
|

Psylloidea (Hemiptera) of Jordan

Abstract: Twenty-two species of Psylloidea are recorded for the first time from Jordan. This raises the number of Psylloidea known from Jordan to 33 species. Euphy/lura olMna and Cacopsylla pyr/cola are deleted from the psylloid fauna of Jordan. The distribution of Psylloidea within and outside Jordan is given as well as host plants and zoogeographic affinities.Kurzfassung: 22 Psylloidea-Arten werden zum ersten Mal in Jordanien nachgewiesen. Dies erhllht die Zahl der aus Jordanicn bekannten Psylloidea-Arten auf 33. Euph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…(Conci et al, 1993). M. gallicola has so far been known to occur in Bulgaria, Greece, Montenegro, Lebanon, Israel and Jordan (Burckhardt & Lauterer, 1989;Al Khawaldeeh et al, 1997;Zeidan-Gèze & Burckhardt, 1998;Souliotis & Tsourgianni, 2000). Our recent investigation has revealed that it is fairly frequent on Pistacia terebinthus also on temperate carstic slopes in south-western part of Slovenia.…”
Section: Allmentioning
confidence: 99%
“…(Conci et al, 1993). M. gallicola has so far been known to occur in Bulgaria, Greece, Montenegro, Lebanon, Israel and Jordan (Burckhardt & Lauterer, 1989;Al Khawaldeeh et al, 1997;Zeidan-Gèze & Burckhardt, 1998;Souliotis & Tsourgianni, 2000). Our recent investigation has revealed that it is fairly frequent on Pistacia terebinthus also on temperate carstic slopes in south-western part of Slovenia.…”
Section: Allmentioning
confidence: 99%
“…The pest has been known in the Middle East for a long time but has been misidentified as A. targionii (Lichtenstein, 1874) in Iran (Davatchi, 1958) or A. succincta (Heeger, 1856) in Türkiye (Çelik, 1981) prior to the taxonomic revision of Burckhardt and Lauterer (1989), who reported the species from Armenia, Bulgaria, Georgia, Iraq, Iran, Israel, Tajikistan, Türkiye and the Crimea (Ukraine). Subsequently, A. pistaciae has also been recorded from Afghanistan, Azerbaijan, Greece, Jordan, Kyrgyzstan, Lebanon and Turkmenistan (Al‐Khawaldeh et al, 1997; Gegechkori & Loginova, 1990; Lauterer et al, 1998; Zeidan‐Gèze & Burckhardt, 1998). The report of A. targionii on pistachio from Syria (Lababidi & Zebitz, 1995) needs verification as it is probably a misidentification of A. pistaciae .…”
Section: Introductionmentioning
confidence: 99%
“…Mustafa (1991) recorded Bactericera tremblayi (Wagner, 1961). Al Khawaldeh et al (1997) recorded seven species: the polyphagous Bactericera nigricornis (Foerster, 1848) and Bactericera tremblayi (Wagner, 1961) were found on a variety of herbaceous plants, Trioza buxtoni Laing, 1924 was collected from Ficus carica L. and Ficus pseudosycomorus Decaisne (Moraceae), Trioza chenopodii Reuter, 1876 and Trioza dichroa Scott, 1879 were found on Atriplex spp., Chenopodium spp. and other Chenopodiaceae, Trioza galii Foerster, 1848 was collected from Galium spp.…”
Section: Introductionmentioning
confidence: 99%
“…Mustafa (1991) recorded Bactericera tremblayi (Wagner, 1961). Al Khawaldeh et al (1997) Conci and Tamanini (1986) erected the genus Lauritrioza to include the type species Trioza alacris Flor, 1861. Lauritrioza alacris (syn.…”
Section: Introductionmentioning
confidence: 99%